Titanium dioxide / vat yellow GCN composite photocatalyst and preparation method thereof

The titanium dioxide/reduced yellow GCN composite photocatalyst prepared by hydrothermal treatment and hydrothermal doping methods solved the problem of low efficiency in dye wastewater treatment, achieved efficient degradation of methyl orange and rhodamine B, and demonstrated good Photocatalytic stability and performance improvement.

CN119303637APending Publication Date: 2025-01-14YANCHENG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411372739.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The prior art is difficult to operate and low efficiency in dye wastewater treatment, and there is little research on titanium dioxide photocatalysts in regulating crystal surfaces, which affects their performance.

Method used

Titanium dioxide/reduced yellow GCN composite photocatalyst was prepared by hydrothermal treatment and hydrothermal doping methods. By optimizing reaction conditions and component ratios, catalytic performance was improved, and efficient degradation of methyl orange and rhodamine B was achieved.

Benefits of technology

The photocatalytic performance of reducing yellow GCN was improved, and the degradation rate of methyl orange reached 96.02% and the degradation rate of rhodamine B reached 100%, and good photocatalytic stability was maintained, with a degradation rate of more than 80%, which proved that The effectiveness of the hydrothermal doping method is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303637A_ABST
    Figure CN119303637A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium dioxide / vat yellow GCN composite photocatalyst and a preparation method thereof.The photocatalytic efficiency of vat yellow GCN is improved by doping titanium dioxide, the optimal photocatalytic effect is achieved by adjusting the doping proportion, the highest degradation rate of titanium dioxide / vat yellow GCN to methyl orange reaches 96.02%, and the degradation rate of titanium dioxide / vat yellow GCN to rhodamine B reaches 100%; oH plays a main role in a methyl orange photodegradation process of the titanium dioxide / vat yellow GCN composite photocatalyst, and O2 <-> and h < + > also participate in the degradation process; the titanium dioxide / vat yellow GCN composite photocatalyst has good photocatalytic stability, still has a good degradation effect on methyl orange after being used for three times, the degradation rate is higher than 80%, and the titanium dioxide / vat yellow GCN composite photocatalyst has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysts, and in particular relates to a titanium dioxide / reduced yellow GCN composite photocatalyst and a preparation method thereof. Background Art

[0002] Reduced Yellow GCN, reduced yellow-green copper ammonium tungstate molybdate (Reduced Green Copper Nitrate), is a bright yellow with a bright color. It is used as a reducing dye in the printing and dyeing industry. At the same time, Reduced Yellow GCN belongs to the anthraquinone compound and also has good light absorption and conductivity properties.

[0003] Titanium dioxide offers safety, optimal concealing properties, and optimal whiteness and gloss. Titanium dioxide photocatalysts can undergo multiple photocatalytic cycles, continuously absorbing light energy, exciting electrons, transferring electrons, and producing active substances, thereby achieving continuous catalytic reactions. However, TiO2 also suffers from drawbacks such as a wide bandgap and the ease with which excited states can bind. While some researchers have sought to improve material performance through methods such as element doping and altering crystal type and particle size, relatively little research has been conducted on manipulating TiO2 crystal surfaces.

[0004] The methods for treating dye wastewater include adsorption, chemical oxidation, membrane separation, etc. The existing technologies have disadvantages such as difficult operation and low efficiency. Therefore, it is of great significance to explore more efficient dye wastewater treatment technologies. Summary of the Invention

[0005] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract and title of this application to avoid obscuring the purpose of this section, the abstract and the title of the invention, and such simplifications or omissions should not be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a composite photocatalyst of titanium dioxide / reduced yellow GCN.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0009] Reduced yellow GCN is added to NaOH solution, sodium dithionite and thiourea dioxide are added, and the reaction yields solution I;

[0010] Solution I was added with H2O2, stirred, centrifuged, washed, and dried to obtain vat yellow GCN nanopowder;

[0011] Titanium dioxide and vat yellow GCN nanopowders are dispersed in distilled water, subjected to hydrothermal reaction, centrifugally dried and ground to obtain titanium dioxide / vat yellow GCN composite photocatalyst powder.

[0012] As a preferred embodiment of the method for preparing the composite photocatalyst of titanium dioxide / reduced yellow GCN according to the present invention, the mass ratio of the reduced yellow GCN, NaOH and sodium dithionite is 2:2.25 to 2.5:3.

[0013] As a preferred embodiment of the method for preparing the titanium dioxide / vat yellow GCN composite photocatalyst of the present invention, the mass of the vat yellow GCN is 3 to 12 g.

[0014] As a preferred embodiment of the method for preparing the composite photocatalyst of titanium dioxide / vat yellow GCN of the present invention, the reaction temperature is 70-80° C. and the reaction time is 20-25 minutes.

[0015] As a preferred solution of the method for preparing the titanium dioxide / vat yellow GCN composite photocatalyst of the present invention, the volume ratio of the H2O2 to the solution I is 1:37.5-45.

[0016] As a preferred embodiment of the method for preparing the titanium dioxide / vat yellow GCN composite photocatalyst of the present invention, the mass ratio of the titanium dioxide to the vat yellow GCN nanopowder is 1:1-10.

[0017] As a preferred embodiment of the method for preparing the titanium dioxide / vat yellow GCN composite photocatalyst of the present invention, the mass ratio of the titanium dioxide to the vat yellow GCN nanopowder is 1:1-5.

[0018] As a preferred embodiment of the method for preparing the composite photocatalyst of titanium dioxide / vat yellow GCN of the present invention, the temperature of the hydrothermal reaction is 90-100°C.

[0019] As a preferred embodiment of the method for preparing the composite photocatalyst of titanium dioxide / vat yellow GCN of the present invention, the time of the hydrothermal reaction is 1 to 1.5 hours.

[0020] Another object of the present invention is to overcome the deficiencies in the prior art and provide a titanium dioxide / reduced yellow GCN composite photocatalyst prepared by a method for preparing the titanium dioxide / reduced yellow GCN composite photocatalyst, wherein the titanium dioxide / reduced yellow GCN composite photocatalyst has a degradation rate of 96.02% for methyl orange and a degradation rate of 100% for rhodamine B.

[0021] Beneficial effects of the present invention:

[0022] (1) The present invention adopts hydrothermal treatment + hydrothermal doping to prepare titanium dioxide / reduced yellow GCN composite photocatalyst. Titanium dioxide improves the photocatalytic performance of reduced yellow GCN and achieves efficient degradation of methyl orange and rhodamine B through optimization. The degradation rate of methyl orange is as high as 96.02%, and the degradation rate of rhodamine B is 100%.

[0023] (2) The titanium dioxide / reduced yellow GCN composite photocatalyst of the present invention has good photocatalytic stability and still has a good degradation effect on methyl orange after being used three times, with a degradation rate of more than 80%.

[0024] (3) Through the comparative experiment of the effect of different capture agents on the photodegradation rate, the mechanism of degradation of methyl orange by titanium dioxide / reduced yellow GCN composite photocatalyst was explored. ·OH plays a major role in the photodegradation of methyl orange by titanium dioxide / reduced yellow GCN composite photocatalyst. ·O2 - and h + Also involved in the degradation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive effort. Among them:

[0026] Figure 1 This is a diagram showing the photocatalytic cyclic degradation rate of methyl orange solution by titanium dioxide / reduced yellow GCN composite photocatalyst under simulated ultraviolet-visible light in Example 1 of the present invention.

[0027] Figure 2 This is a comparison chart of the photocatalytic degradation effects of catalysts obtained by different treatment methods in Comparative Example 1 and Example 1 of the present invention.

[0028] Figure 3 This is a diagram of the photocatalytic degradation rate constants of the catalysts obtained by different treatment methods in Comparative Example 1 and Example 1 of the present invention.

[0029] Figure 4 These are the photocurrent diagrams of the untreated reduced yellow GCN in Comparative Example 1 of the present invention, the reduced yellow GCN obtained by redox treatment, and the titanium dioxide / reduced yellow GCN composite photocatalyst in Example 1.

[0030] Figure 5 This is a comparison chart of the degradation effects of the titanium dioxide / vat yellow GCN composite photocatalyst at different compounding ratios in Example 1 and Example 2.

[0031] Figure 6This is a diagram of the photocatalytic degradation rate constants of the titanium dioxide / reduced yellow GCN composite photocatalyst at different compounding ratios in Examples 1 and 2 of the present invention.

[0032] Figure 7 This is a comparison chart of the degradation rate constant and degradation rate of the titanium dioxide / reduced yellow GCN composite photocatalyst under different scavengers in Example 3 of the present invention.

[0033] Figure 8 This is a diagram showing the degradation effect of Rhodamine B by titanium dioxide / reduced yellow GCN in Example 4 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0036] Secondly, the term "one embodiment" or "embodiment" herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive of other embodiments.

[0037] Photocatalytic degradation experiment:

[0038] Weigh 0.1g of photocatalyst and pour it into a 250mL beaker. Add 100mL of methyl orange (MO) solution with a concentration of 10mg / L as a simulated pollutant. Place the beaker in a magnetic stirring device to ensure that the catalyst and pollutant solution are fully mixed. Stir evenly in the dark at room temperature of 25℃ for 30min to simulate the light-shielding adsorption process. After 30min, take out 5mL of the reaction solution. Centrifuge using a micro high-speed desktop centrifuge to separate the solid catalyst and the solution. Aspirate the clarified solution and measure its absorbance value on a UV-visible spectrophotometer.

[0039] After the light-shielding adsorption experiment, the suspension is considered to have reached adsorption-desorption equilibrium. A xenon lamp was turned on to simulate visible light irradiation. A photocatalytic degradation experiment was conducted under visible light irradiation, with 5 mL of the reaction solution withdrawn every 10 minutes until the reaction had proceeded for 1 hour. Each withdrawn suspension was centrifuged in a micro high-speed desktop centrifuge to obtain a clear solution. The absorbance of the clear solution was measured using a UV-visible spectrophotometer at the maximum absorption wavelength of the pollutant to be degraded.

[0040] Active group capture experiment:

[0041] Add 0.1g of composite photocatalyst and 100mL of 10mg / L methyl orange (MO) solution into a 250mL beaker, then add 1mL of p-benzoquinone solution, EDTA-2Na solution and isopropanol solution respectively, then stir magnetically in the dark for 30min, then irradiate under simulated ultraviolet-visible light and simulated visible light, take the solution after every 10min, for a total of 1h, centrifuge, take the supernatant to test the absorbance and analyze.

[0042] 0.1g of sample was added to 100mL of MO solution at a concentration of 10mg / L. The solution was then stirred for 30 minutes in a darkened state to achieve equilibrium between adsorption and desorption. The sample was then irradiated with a 300W xenon lamp (simulating UV light) for 60 minutes. The liquid was collected every 10 minutes and centrifuged. The upper layer was aspirated and the absorbance was measured.

[0043] Finally, the photodecomposition rate of the sample to the liquid is calculated according to formula (1).

[0044]

[0045] Where: η—photodegradation rate, %;

[0046] A0—absorbance of MO solution without light exposure;

[0047] A t —The absorbance of MO solution at t.

[0048] According to formula (2), the Langmuir-Hinshelwood pseudo-first-order reaction kinetic model was used to study the photocatalytic degradation rate of the sample to MO aqueous solution. t The ratio of A0 to A t .

[0049]

[0050] Where: K—photodegradation rate, / min;

[0051] C0—Concentration of MO solution without light exposure, mg / L;

[0052] C t —Concentration of MO solution at illumination time t, mg / L.

[0053] Example 1

[0054] This embodiment provides a method for preparing a titanium dioxide / vat yellow GCN composite material:

[0055] After hydrothermal treatment, vat yellow GCN nanopowder was obtained. 150 mL of deionized water, 6.75 g of sodium hydroxide, 6 g of vat yellow GCN dye, 2.25 g of thiourea dioxide, and 9 g of hydrosulfite were placed in a round-bottom flask and stirred with a rotor. The mixture was placed in a 70°C oil bath for 20 minutes to obtain Solution I.

[0056] Pour 4 mL of hydrogen peroxide, with a volume ratio of H2O2 to the solution I of 1:37.5, stir with a stirring rod and let stand for 12 to 24 hours to obtain vat yellow GCN. Place the complex in a centrifuge, set the centrifugal speed to 12,000 revolutions per minute, and the centrifugation time to 3 minutes. Pour off the upper liquid, retain the precipitate, rinse with water and shake well, perform ultrasonic treatment, repeat the centrifugation step 3 times, then dry the sample, and finally grind and collect it to obtain vat yellow GCN nanopowder.

[0057] To hydrothermally dope titanium dioxide, 1.0097g of titanium dioxide and vat yellow GCN nanopowder were added to distilled water and sonicated for 30 minutes. The mass ratio of titanium dioxide to vat yellow GCN nanopowder was 1:1. The mixture was then hydrothermally treated at 100°C for 1 hour. The centrifugally dehydrated sample was then dried and ground to produce a titanium dioxide / vat yellow GCN photocatalyst.

[0058] Figure 1 This simulated photocatalytic degradation rate of MO solution using a titanium dioxide / reduced yellow GCN composite photocatalyst under UV-visible light is shown in this example. As can be seen, the titanium dioxide / reduced yellow GCN composite photocatalyst achieved a 96.02% degradation rate of methyl orange after one hour. Even after three repeated uses, the degradation rate remained at 80%, demonstrating the excellent photocatalytic stability of the titanium dioxide / reduced yellow GCN composite photocatalyst.

[0059] Comparative Example 1

[0060] The difference between this comparative example and Example 1 is that the catalyst is prepared by different treatment methods, specifically:

[0061] Dry cylinder treatment (redox treatment): Take 150mL of deionized water, 6.75g of sodium hydroxide, 6g of vat yellow GCN dye, 2.25g of thiourea dioxide, and 9g of hydrosulfite, put them into a round-bottom flask, then put in a rotor to stir and compound to obtain vat yellow GCN.

[0062] Hydrothermal treatment: Only the hydrothermal treatment in Example 1 was performed to obtain vat yellow GCN nanopowder.

[0063] Dry-cylinder doping: The hydrothermal doping treatment in Example 1 was replaced with dry-cylinder doping of titanium dioxide, i.e., 1.0097 g of titanium dioxide was added to distilled water and ultrasonicated for 30 minutes, and then added to Solution I and compounded with titanium dioxide and vat yellow GCN in a mass ratio of 1:1. Finally, the titanium dioxide was allowed to stand for 12 hours, and the titanium dioxide / vat yellow GCN composite photocatalyst was obtained by centrifugal drying and grinding.

[0064] Comparison of the degradation effects of the above materials, the untreated initial reduced yellow GCN, and the titanium dioxide / reduced yellow GCN composite photocatalyst obtained by hydrothermal doping treatment in Example 1 on methyl orange simulated wastewater. Figure 2 It can be seen that the titanium dioxide / reduced yellow GCN composite photocatalyst obtained by hydrothermal doping treatment has the best photocatalytic effect, and the degradation rate of methyl orange reaches 96.02% after 60 minutes.

[0065] Figure 3 The figure shows the photocatalytic degradation rate constants obtained by different treatment methods. It can be seen that the photocatalytic degradation rate constant of the titanium dioxide / reduced yellow GCN composite photocatalyst in Example 1 is the largest and the degradation efficiency is the highest. After hydrothermal treatment, a composite material with higher photocatalytic efficiency can be obtained. Hydrothermal treatment can not only promote the interaction and structural stability between materials, but also improve the crystallinity and specific surface area of ​​the material through high temperature and high pressure environment. Hydrothermal doping treatment enhances the photocatalytic effect by changing the electronic structure of the photocatalyst, enhancing the efficiency of photogenerated charge separation, improving light absorption capacity, optimizing surface properties and enhancing stability. Compared with hydrothermal treatment alone, better photocatalytic performance can be obtained by using hydrothermal doping treatment. Hydrothermal doping treatment not only helps the formation of composite materials, but also can adjust the electronic properties of materials by introducing compounding agents. The untreated titanium dioxide and reduced yellow GCN composite powder has the worst photocatalytic effect, which may be due to uneven compounding and incomplete reaction.

[0066] Figure 4 The photocurrent graphs for untreated reduced yellow GCN, the titanium dioxide / reduced yellow GCN composite photocatalyst obtained by hydrothermal doping in Example 1, and reduced yellow GCN obtained by redox treatment are shown. It can be seen that the hydrothermal doping treatment facilitates the separation of photogenerated charges, thereby enhancing photocurrent generation. After the redox reaction, the material's conductivity and photogenerated charge separation efficiency improve only slightly.

[0067] Example 2

[0068] The difference between this embodiment and embodiment 1 is that the mass ratio of titanium dioxide and vat yellow GCN is adjusted to 1:5 and 1:10, and the other steps are the same as those in embodiment 1 to prepare titanium dioxide / vat yellow GCN composite photocatalysts with different ratios.

[0069] Comparing the photocatalytic performance of the above catalyst with that of the titanium dioxide / reduced yellow GCN composite photocatalyst of Example 1 and the titanium dioxide / reduced yellow GCN composite photocatalyst obtained by dry cylinder doping in Comparative Example 1, the photocatalytic degradation effects of different photocatalysts on methyl orange under ultraviolet light or visible light irradiation are as follows: Figure 5 、 6 shown.

[0070] Depend on Figure 5 It can be seen that the 1:1 visible light refers to the degradation of methyl orange under visible light. It can be seen that the titanium dioxide / vat yellow GCN composite photocatalyst in Example 1 has the highest degradation rate, reaching 96.02%.

[0071] Depend on Figure 6 It can be seen that the effect and speed of photocatalytic degradation will change with the change of the mass ratio of titanium dioxide and vat yellow GCN. In Example 1, the titanium dioxide / vat yellow GCN composite photocatalyst has the highest degradation rate and the highest catalytic efficiency.

[0072] When the mass ratio of titanium dioxide to reduced yellow GCN is 1:1, hydrothermal treatment can improve the crystal structure and specific surface area of ​​the material, and the material will show a higher photocatalytic effect and reaction rate. The mass ratios of 1:5 and 1:10 improve the separation efficiency of photogenerated charges and the light absorption capacity, and the photocatalytic efficiency and rate constant decrease. For dry-cylinder-doped catalysts under visible light irradiation, TiO2 mainly absorbs ultraviolet light and has poor absorption capacity for visible light. The proportion of ultraviolet light in visible light is low, which limits the effectiveness of the photocatalyst under natural light conditions, resulting in a poor photocatalytic degradation rate.

[0073] Example 3

[0074] This example compares the effects of different capture agents (isopropyl alcohol, p-benzoquinone, and disodium EDTA) on the photodegradation rate of the titanium dioxide / reduced yellow GCN composite photocatalyst in Example 1. Figure 7 As shown. It can be seen that after adding the capture agent, the photocatalytic degradation rate of methyl orange by the photocatalyst is significantly reduced. After adding EDTA-2Na, IPA and BQ, the degradation rate of MO decreased from 96.02% to 89.08%, 90.73% and 91.05% respectively. EDTA-2Na, IPA and BQ capture holes (h + ), hydroxyl radicals (·OH) and superoxide radicals (·O2 - ), indicating that hydroxyl radicals (·OH) play a major role in the photodegradation of methyl orange, ·O2- and h + Also involved in the degradation process.

[0075] Example 4

[0076] This example uses the titanium dioxide / reduced yellow composite photocatalyst of Example 1 for photocatalytic degradation of rhodamine B. The degradation experimental steps are the same as those for methyl orange. The degradation effect is as follows: Figure 8 As shown in Figure 2, Rhodamine B was completely degraded after 3 min.

[0077] Comparative Example 2

[0078] This comparative example differs from Example 1 in that the catalyst was prepared by adjusting the ratio of titanium dioxide to GCN to 0.5:1. The resulting catalyst was less effective in degrading methyl orange than simply reducing GCN, and had poor photocatalytic stability.

[0079] In summary, the present invention improves the photocatalytic performance of vat yellow GCN by compounding titanium dioxide, and achieves efficient degradation of methyl orange and rhodamine B through optimization, with a degradation rate of 96.02% for methyl orange and 100% for rhodamine B. The composite photocatalyst of the present invention has good photocatalytic stability and still has a good degradation effect on methyl orange after three uses, with a degradation rate of more than 80%. ·OH plays a major role in the photodegradation process of methyl orange, ·O2 - and h + Also involved in the degradation process.

[0080] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a titanium dioxide / reduced yellow GCN composite photocatalyst, characterized in that: include, Reduced yellow GCN is added to NaOH solution, sodium dithionite and thiourea dioxide are added, and the reaction obtains solution Ⅰ; Solution I was added with H2O2, stirred, centrifuged, washed and dried to obtain reduced yellow GCN nanopowder; Titanium dioxide and reduced yellow GCN nanopowders are dispersed in distilled water, subjected to hydrothermal reaction, centrifugally dried and ground to obtain titanium dioxide / reduced yellow GCN composite photocatalyst powder.

2. The method for preparing the titanium dioxide / reduced yellow GCN composite photocatalyst according to claim 1, characterized in that: The mass ratio of the vat yellow GCN, NaOH and sodium dithionite is 2:2.25 to 2.5:

3.

3. The method for preparing the titanium dioxide / reduced yellow GCN composite photocatalyst as claimed in claim 2, characterized in that: The mass of the vat yellow GCN is 3 to 12 g.

4. The method for preparing the titanium dioxide / reduced yellow GCN composite photocatalyst according to claim 1, characterized in that: The reaction temperature is 70-80°C and the reaction time is 20-25 minutes.

5. The method for preparing the titanium dioxide / reduced yellow GCN composite photocatalyst according to claim 1, characterized in that: The volume ratio of the H2O2 to the solution I is 1:37.5-45.

6. The method for preparing the titanium dioxide / reduced yellow GCN composite photocatalyst according to claim 1, characterized in that: The mass ratio of the titanium dioxide to the reduced yellow GCN nano powder is 1:1-10.

7. The method for preparing the titanium dioxide / reduced yellow GCN composite photocatalyst as claimed in claim 6, characterized in that: The mass ratio of the titanium dioxide to the reduced yellow GCN nano powder is 1:1-5.

8. The method for preparing the titanium dioxide / reduced yellow GCN composite photocatalyst as claimed in claim 1, characterized in that: The temperature of the hydrothermal reaction is 90-100°C.

9. The method for preparing the titanium dioxide / reduced yellow GCN composite photocatalyst as claimed in claim 8, characterized in that: The hydrothermal reaction time is 1 to 1.5 hours.

10. The titanium dioxide / reduced yellow GCN composite photocatalyst prepared by the method for preparing the titanium dioxide / reduced yellow GCN composite photocatalyst according to any one of claims 1 to 9, characterized in that: The degradation rate of the titanium dioxide / reduced yellow GCN composite photocatalyst to methyl orange is 96.02%, and the degradation rate to rhodamine B is 100%.